2002
DOI: 10.1002/immu.200390013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental African trypanosomiasis: IFN‐γ mediates early mortality

Abstract: In this study, we demonstrate that Kupffer cells in the livers of highly susceptible BALB/c mice infected with Trypanosoma congolense were loaded with trypanosomal antigen and appeared highly activated. This was associated with an enlarged capillary bed in the livers and decreased blood pressure of these mice towards the terminal stage. Blocking of murine IL‐10 receptor (IL‐10R)in vivo shortened the survival time of highly susceptible T. congolense‐infected BALB/c mice. Anti‐IL‐10R treatment decreased the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
146
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(158 citation statements)
references
References 31 publications
11
146
1
Order By: Relevance
“…Thus, during African trypanosomosis, hypersecretion of IFN-, with a concomitant suppression of IL-10, results in profound increase in the IFN-/IL-10 ratio, macrophage hyperactivation with excessive TNF-and NO production and a susceptible phenotype [10]. In agreement with previous reports [11,15,16], IL-10 could play an important role in trypanotolerance by means of checking the levels of IFN- production during the course of infection.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Thus, during African trypanosomosis, hypersecretion of IFN-, with a concomitant suppression of IL-10, results in profound increase in the IFN-/IL-10 ratio, macrophage hyperactivation with excessive TNF-and NO production and a susceptible phenotype [10]. In agreement with previous reports [11,15,16], IL-10 could play an important role in trypanotolerance by means of checking the levels of IFN- production during the course of infection.…”
Section: Discussionsupporting
confidence: 85%
“…This study further suggests that the production of various immune molecules during trypanosomosis is under tight control. Thus, there seems to be a certain range within which pro-inflammatory and associated molecules are protective, above which they become harmful to the host, possibly through host-tissue damage [11,15], and below which they fail to induce an effective parasite control, leading to massive parasitosis [3,11]. Of note, the IFN-/IL-10 balance appears to be critical [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of the host-parasite relationship is demonstrated by multiple effects of IFN-␥ as well as IL-10 in African trypanosomiasis. IFN-␥ is mediating mortality in susceptible BALB/c mice infected with T. congolense (12,37) and immunopathology in infected, relatively resistant C57BL/6 mice (34) but is also required for survival (25). IL-10 down-regulates production of IFN-␥ and the immunopathology in trypanosome-infected mice (12,34,38) but also suppresses protective immune responses (39).…”
Section: Discussionmentioning
confidence: 99%
“…infection with 10 3 T. congolense clone 13 (TC13), whereas relatively resistant C57BL/6 mice survive for Ͼ100 days, a survival associated with cycles of parasitemia and expression of new VSGs (11). We have shown that the early mortality in highly susceptible BALB/c mice infected with T. congolense or T. brucei is caused by an excessive activation of the macrophage system, associated with an excessive production of IFN-␥ and a systemic inflammatory response syndrome (12)(13)(14).…”
Section: Trypanosoma Brucei Gambiense and Trypanosoma Brucei Rhodesiementioning
confidence: 99%